2020
DOI: 10.1186/s12860-020-00256-3
|View full text |Cite
|
Sign up to set email alerts
|

PGRMC1 phosphorylation affects cell shape, motility, glycolysis, mitochondrial form and function, and tumor growth

Abstract: Background Progesterone Receptor Membrane Component 1 (PGRMC1) is expressed in many cancer cells, where it is associated with detrimental patient outcomes. It contains phosphorylated tyrosines which evolutionarily preceded deuterostome gastrulation and tissue differentiation mechanisms. Results We demonstrate that manipulating PGRMC1 phosphorylation status in MIA PaCa-2 (MP) cells imposes broad pleiotropic effects. Relative to parental cells over-expressing hemagglutinin-tagged wild-type (WT) PGRMC1-HA, cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…Altered mitochondrial biology was also associated with PGRMC1-driven changes in glycolysis [ 63 ], concordant with our earlier hypothesis that PGRMC1 could be associated with the Warburg effect. In 2019, Sabbir independently demonstrated that HEK293 cells induced aerobic glycolysis upon P4 treatment, which involved altered abundance of post-translationally modified PGRMC1 isoforms.…”
Section: Recent Advances and Current Statussupporting
confidence: 90%
See 1 more Smart Citation
“…Altered mitochondrial biology was also associated with PGRMC1-driven changes in glycolysis [ 63 ], concordant with our earlier hypothesis that PGRMC1 could be associated with the Warburg effect. In 2019, Sabbir independently demonstrated that HEK293 cells induced aerobic glycolysis upon P4 treatment, which involved altered abundance of post-translationally modified PGRMC1 isoforms.…”
Section: Recent Advances and Current Statussupporting
confidence: 90%
“…Somehow, this seemed to be related to mitochondrial function [ 56 ], and we showed that PGRMC1 phosphorylation status can exert the most dramatic effects on mitochondrial form (fission versus fusion) and cell metabolism. This involved not just mitochondria, but also the PI3K/Akt pathway via tyrosine 180 [ 63 ]. PGRMC1 modulation of the Akt pathway has been reported multiple times [ 4 , 64 , 65 ].…”
Section: Recent Advances and Current Statusmentioning
confidence: 99%
“…It is worth noting that in this study, 8 (ACTR3, ARF4, PGRMC1, RPS23, WDR12, ACTR2, SIAH1, and RPS27L) of 12 hub genes are related to cancers, such as lung cancer, epithelial ovarian cancer, gastric cancer, glioblastoma, breast cancer, and esophageal cancer (51,54,(57)(58)(59)(60)(61)(62)(63). A last year's research showed pulmonary adenocarcinoma cells around the ossification expressed bone morphogenetic protein-2 and osteopontin, which generally induce and stimulate bone formation (64,65).…”
Section: Discussionmentioning
confidence: 71%
“…First, we observed that genetic deletion or silencing of Pgrmc1 resulted in decreased expression of FAK, which was shown to negatively regulate invadopodia and positively regulate the invasion of breast cancer cells [ 27 ]. A recent study showed that the PGRMC1 protein is post-translationally modified or phosphorylated by progesterone [ 28 ], and that its phosphorylation influences the activation of FAK and alters the cellular migration depending on the phosphorylation site [ 29 ]. Also, similar to a previous study that demonstrated the lack of lung metastasis in FAK-deficient PyMT mice [ 30 ], the FAK expression was suppressed in Pgrmc1 KO mice in this study.…”
Section: Discussionmentioning
confidence: 99%